Pathogenicity of Fusarium species causing head blight in barley - Xue, Allen; Ho, Keh; Butler, Gail; Vigier, Bernard; Babcock, Carolyn (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2006)
AbstractThe pathogenicity of eight Fusarium species causing fusarium head blight (FHB) in barley was studied under controlled conditions. Six barley genotypes varying in resistance to FHB were artificially inoculated with six isolates each of F. acuminatum, F. avenaceum, F. crookwellense, F. culmorum, F. equiseti, F. graminearum, F. poae and F. sporotrichioides 10-14 d after heading. Symptoms of FHB were rated as disease severity using a 0-9 scale, 4, 7, 14, 21 and 28 d after inoculation, and as percentage of infected spikelets (IS) after 21 d. All species tested caused head blight symptoms on the barley genotypes, but only F. crookwellense, F. culmorum and F. graminearum resulted in severe disease development (> 65% IS) and were considered highly pathogenic. Fusarium avenaceum had 48% IS, which was significantly lower than those of the three highly pathogenic species and was moderately pathogenic. The remaining species had < 15% IS and were weakly pathogenic. There were significant differences (P < 0.05) in aggressiveness among isolates within species and in susceptibility among barley genotypes, suggesting that screening for resistance to FHB requires the use of aggressive isolates or a mixture of several isolates. This is the first report showing that F. crookwellense is highly pathogenic and F. avenaceum is moderately pathogenic on barley.